Successful Clinical Management of Dystocia due to Fetal Emphysema in a Buffalo - Rashid, Muzamil; Chandra, Pradeep; Kumar, Naveen; Singh, Mohar; Kumar, Abhishek; Vandana; Kumar, Brijesh (The Indian Journal of Animal Reproduction, 2022)
A non-descript buffalo in second parity presented to Referral Veterinary Polyclinic, ICAR-IVRI, Izatnagar with history of complete gestation length and inability to calve since 36 h despite continuous straining to deliver the fetus. The case was attended by local practitioner but failed to extract out the calf. A foul vaginal discharge was noticed with bilateral distension of abdomen. The case was diagnosed as dystocia due to emphysematous fetus and successfully managed through cesarean section.